Learning from cross country difference of female work participation in agriculture in the Eastern Gangetic Basin: The macro and micro connections - Sen, Sucharita (Jawaharlal Nehru University, 2019)
Presented by Sucharita Sen (JNU), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.